Low-temperature processing of superconducting Tl2Ba2Ca1Cu2Ox films on CeO2 buffered sapphire - OConnor, J; DewHughes, D; Bramley, A; Grovenor, C; Goringe, M; Morley, S (1996)
Tl2Ba2Ca1Cu2Ox thin films with excellent alignment have been grown on CeO2 buffered R-plane sapphire using an ex situ anneal step in argon atmospheres at temperatures of 720-740°C. With this low-temperature process we have overcome the serious problem of reaction layers being formed at the CeO2/Tl2Ba2Ca1Cu2O x interface, which can degrade film properties. The presence of a sharp CeO2/Tl2Ba2Ca1Cu2O x interface has been confirmed by x-ray diffraction, transmission electron microscopy, and high resolution electron microscopy observations. Films have well connected morphologies, with critical temperature (Tc) values of up to 101.6 K and critical current density (Jc) values of up to 1.25 × 105 A cm-2. © 1996 American Institute of Physics.